Atom land : a guided tour through the strange (and impossibly small) world of particle physics - Butterworth, Jon (The Experiment, LLC, 2018)
"This book brings the impossibly small world of particle physics to life, taking readers on a guided journey through the subatomic world. With maps to help "guide" the reader through "Atom Land" along the way, as they learn about "electron ports," "boson continents," "hadron islands," and more"--